Tibiocalcaneal arthrodesis using an Ilizarov fixator() - Leite, Alessandro Marcondes (Rev Bras Ortop, 2013)
OBJECTIVE: To evaluate the results of arthrodesis with Ilizarov fixator with tibiocalcaneana. METHODS: We studied 12 patients with a mean age of 35 years, and 9 (75%) men and 3 (25%) women, underwent arthrodesis tibiocalcaneana. The diagnosis in the preoperative talus infection. We used a modified surgical technique Reckling (6 patients) and the Ilizarov technique, modified by Catagni (6 patients). Patients were evaluated by the AOFAS scale research and patient satisfaction. RESULTS: Union was achieved in 100% of cases. The mean time to healing was 6 months (range 4-12 months) and mean duration of external fixator removal was 9 months (range 4-13 months). Stretching was performed in 6 patients with an average of 4 cm. The follow-up with Vancomycin lasted around 6 months. The average AOFAS score was 72.5 points (range 57 to 89 points). All patients were satisfied with the result. CONCLUSION: Despite the small number of cases, arthrodesis tibiocalcaneana seemed to be a good solution for cases of complex pathologies of the talus, such as infection, resulting in bone healing, pain relief and patient satisfaction.